Estimation of total contamination of the clarifier of waste water in the town of Zhanaozen (Eurasian Journal of Ecology, 2020)
The article presents the results of the degree of contamination of the settling tank and calculates thehydrochemical index of contamination. In the city of oil workers Zhanaozen insufficiently treated wastewater (WW) from municipal sewage treatment plants is discharged into a sump, which is a partially collapsed earthen container. The sump constantly contains waste water of various degrees of contamination, which are in it until a certain “critical” time. The special role of the sump is WW, being locatedwithin the city limits, it is almost a “man-made” object, which is a source of creating a “critical” environmental and sanitary-epidemiological situation for the population. Water and sediment samples wereanalyzed for heavy metals (Cu, Cd, Zn, Cr3+). The total pollution index was calculated to determinethe gross content of heavy metals Cr, Cu, Fe, Zn and metalloid As in bottom sediments. To obtain anobjective assessment of the degree of contamination of bottom sediments with heavy metals, severalindicators of total ZC pollution were used. In settling ponds (buffer ponds), the concentrations of pollutants in suspended solids and in the upper layers of sediments are much higher than the concentrationsof substances dissolved in the water column. The results of the assessment of the calculation of the totalpollution of the settling tank located almost within the city of Zhanaozen, which turns it into a dangerous object, allow us to develop the most economically feasible and environmentally friendly method forwater purification.Key word: Sedimentation tank, bottom sediments, waste water, heavy metals.